Tolerance and potential for bioaccumulation of Alternanthera tenella Colla to cadmium under in vitro conditions - Rodrigues, Luiz Carlos Almeida; Martins, João Paulo Rodrigues; de Almeida Júnior, Osmar; Guilherme, Luiz Roberto Guimarães; Pasqual, Moacir; de Castro, Evaristo Mauro (Plant cell, tissue and organ culture, 2017)
High concentrations of cadmium (Cd) in the environment can threaten the local biota and one of its main sources is anthropic activities such as zinc (Zn) mining. Some plant species are able to tolerate high Cd concentrations, using anatomical and physiological strategies to avoid the absorption or accumulation of this element in their biomass. The in vitro assessment of these strategies is an efficient way to control variables external to the experiment. We aimed to investigate the anatomical and physiological changes in Alternanthera tenella exposed to Cd and its potential for accumulation in controlled microenvironmental conditions. We evaluated changes in the leaf and root anatomy, antioxidant system, and biomass of A. tenella grown in a culture medium containing increasing Cd concentrations (0, 50, 100, and 150 μM), in the presence of 1500 μM Zn. Alternanthera tenella was able to accumulate Cd and Zn and these elements competed for absorption by the species. Increase in Cd in the medium led to a progressive thickening of the root tissues, which was also observed on the leaves, albeit only at concentrations below 100 μM Cd. The concentration of 150 μM Cd was toxic to the leaf tissue and stimulated the formation of hydrogen peroxide, interfering with the antioxidant system and reducing plant biomass and the chlorophyll levels. Therefore, in vitro cultivated A. tenella can accumulate Cd and tolerate up to 100 μM Cd by modifying its anatomy and physiology in order to cope with Cd stress.